Penerapan Model Pembelajaran Discovery Learning untuk Meningkatkan Hasil Belajar Siswa - Pratama, Alvin; Fazera, Della; Fortunata, Lisna Anggia; Manurung, Naomi; Fadilah, Rayhan (Edukhasi: Jurnal Inovasi Pendidikan, 2024)
This classroom action research aims to evaluate the effectiveness of implementing the discovery learning model in improving students' understanding of types of maps at SMA Negeri 3 Medan. This research uses qualitative methods with a classroom action research design. The subjects of this research were class X 11 students at SMA Negeri 3 Medan. Data was collected through observation, learning results tests, and interviews with teachers and students. The results of the research show that the application of the discovery learning model can significantly increase students' understanding of map types. Students are more active in the learning process, gaining a deeper understanding of topographic maps, thematic maps, political maps, and choropleth maps. They also show increased learning motivation in learning activities. This research contributes to the development of learning methods that are more effective in understanding students about types of maps. Recommendations for further research are to expand the scope of subject matter, apply the discovery learning model to other subjects, and involve more research subjects to deepen the analysis of the impact of the discovery learning model on student learning outcomes.